Knowledge of Zika virus disease among reproductive-age women attending a general outpatient clinic in Northern Nigeria. Issue 4 (19th July 2017) - Michael, GC; Aliyu, I; Grema, BA; Ashimi, AO
Abstract : Background: Nigeria is not insulated from the global threat of Zika virus disease (ZVD) because of international travel and the presence of Zika-virus-carrying mosquitoes in the country. A paucity of studies exists concerning knowledge of ZVD among at-risk populations. Thus, the necessity for assessment of knowledge of ZVD among reproductive-age women in general outpatient setting. Materials and methods: A cross-sectional study was conducted on 377 reproductive-age women attending a Nigerian tertiary hospital's general outpatient clinic. Their knowledge of ZVD was assessed using a structured questionnaire. A chi-square test was used to assess the relationship between participants' sociodemographics and ZVD knowledge. Results: The participants' median age was 27.0 ± 7.19 years. Though 68.97% of participants were aware of ZVD, only 23.85% of those had good knowledge of ZVD. Their median knowledge score was 57.14%. Participants' age (< 27 years) ( p = 0.00399), tribe (Hausa) ( p = 0.0174) and monogamous family type ( p = 0.0108) were associated with good knowledge of ZVD. Only 5% knew that ZVD is transmitted through both mosquito bites and a sexual route. Some 80% were unaware that everybody was at risk of ZVD but 80.77% knew it could cause microcephaly. Insecticide-treated nets (80.77%), environmental sanitation (78.08%) and indoor insecticide spraying (58.85%) were preventive measures reported by most participants; a minority reported mosquito repellents (28.46%), wearing of protective clothing (36.15%), and traditional medicines (20.00%) as preventive measures. They lacked knowledge of prevention of sexual transmission. Conclusion: Participants' knowledge of ZVD was inadequate despite the high awareness rate. Stakeholders may need to address existing knowledge gaps through effective public enlightenment.